Positive electrode prelithiation agent, and its preparation method and application
The positive electrode prelithiation agent addresses the challenge of irreversible lithium loss in lithium-ion batteries by using a catalytically active oxide material to release lithium at low potential, enhancing energy density and cycle life while preventing electrolyte gassing and impedance.
Patent Information
- Application Number
- JP2023530320
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-23
- Filing Date
- 2021-07-09
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-07-09
AI Technical Summary
Existing lithium-ion batteries face challenges in achieving high energy density and long cycle life due to irreversible loss of active lithium during battery preparation and cycling, with current cathode prelithiation agents increasing electrochemical cell impedance and risking gassing by the electrolyte.
A positive electrode prelithiation agent using an oxide cathode active material with a specific intensity ratio of crystal plane diffraction peaks, catalyzing lithium-rich materials to release active lithium at low potential, and incorporating a protective layer to prevent impedance and gassing, while maintaining structural stability.
The solution enhances battery performance by fully compensating for irreversible lithium loss, improving energy density and cycle life without increasing cell impedance or gassing risks, and allowing for efficient mass production.
Smart Images

Figure 0007612985000004 
Figure 0007612985000005 
Figure 0007612985000006
Abstract
Description
[Technical field]
[0001] This application claims priority to Chinese Patent Application No. 202011332764.2, entitled "POSITIVE-ELECTRODE PRE-LITHIATION AGENT, AND PREPARATION METHOD AND APPLICATION THEREOF," filed with the State Intellectual Property Office of the People's Republic of China on November 23, 2020, which is incorporated herein by reference in its entirety.
[0002] TECHNICAL FIELD Embodiments of the present application relate to the field of battery technology, and in particular to a cathode prelithiation agent for a battery cathode, and its preparation method and application. [Background technology]
[0003] With the development of economy, science and technology, energy storage devices with high energy density and long cycle life are urgently needed in industries such as portable electronic devices (such as mobile phones, tablet computers and notebook computers), unmanned aerial vehicles and electric vehicles. In order to enable the lithium-ion battery, which is an energy storage device, to meet the above-mentioned requirements, the method commonly used in the industry is to pre-add a pre-lithiation agent capable of supplying active lithium to the lithium-ion battery system to compensate for the irreversible loss of active lithium during battery preparation and cycling.
[0004] Currently, battery prelithiation can be mainly classified into positive prelithiation and negative prelithiation. In positive prelithiation, a positive prelithiation agent is added to the positive system of the battery. Currently, several types of positive prelithiation agents are available, which are usually lithium-rich materials such as Li2NiO2 and Li6CoO4; the residues left on the positive side after delithiation of these positive prelithiation agents will increase the impedance of the electrochemical cell, catalyze the electrolyte to produce gas, etc. Summary of the Invention
[0005] Considering this, the present application provides a cathode prelithiation agent in an embodiment. An oxide cathode active material with an intensity ratio of the crystal plane diffraction peak (003) to the crystal plane diffraction peak (104) less than or equal to 2 is used as a catalyst, which can catalyze the lithium-rich material to release active lithium at a low voltage. In addition, the residue remaining on the cathode side after delithiation of the cathode prelithiation agent does not increase the risk of gas generation by the electrolyte or the impedance of the electrochemical cell. This expands the selection range of the cathode prelithiation agent.
[0006] Specifically, a first aspect of an embodiment of the present application provides a cathode prelithiation agent. The cathode prelithiation agent includes a catalyst and a lithium-rich material. The catalyst is an oxide cathode active material, and an intensity ratio of a crystal plane diffraction peak (003) of the catalyst to a crystal plane diffraction peak (104) of the catalyst is less than or equal to 2, and the catalyst is configured to catalyze and decompose the lithium-rich material to release active lithium. The lithium-rich material includes at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate.
[0007] The positive electrode prelithiation agent provided in this embodiment of the present application includes a lithium-rich material and a catalyst. The catalyst is an oxide positive electrode active material with special XRD characteristics, which has high catalytic activity and can catalyze the lithium-rich material originally having a high delithiation potential to decompose at a low potential and release active lithium ions during the battery formation stage. This expands the selection range of the positive electrode prelithiation agent. The positive electrode prelithiation agent has a high prelithiation capacity and can fully compensate for the irreversible consumption of active lithium in the battery, which helps to improve the battery performance. In addition, although some residue remains on the positive electrode side after the delithiation of the positive electrode prelithiation agent, it does not increase the risk of gas generation by the electrolyte, increase the impedance of the electrochemical cell, or reduce the battery energy density.
[0008] In some implementations of the present application, the intensity ratio of the crystal plane diffraction peak (003) of the catalyst to the crystal plane diffraction peak (104) of the catalyst ranges from 1.0 to 1.8, in which case the catalytic activity of the catalyst is high.
[0009] In one implementation of the present application, the oxide positive electrode active material includes at least one of lithium cobalt oxide, lithium manganate, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganate, lithium nickel cobalt manganate, and lithium nickel cobalt aluminate.
[0010] In some implementations of the present application, the oxide positive electrode active material further includes a doping element, which includes at least one of B, P, N, Mg, Al, Ca, Ba, La, Zr, Mo, Nb, Ti, V, Sn, Sb, Cr, Fe, Cu, and Zn. The appropriate doping element can change the internal electron orbital overlap state or surface properties of the oxide positive electrode active material, improve the structural stability, and so on.
[0011] In one implementation of the present application, the particle size of the catalyst ranges from 10 nm to 25 μm. The particle size of the catalyst may be selected based on the electrochemical activity of the lithium-rich material. For example, if the electrochemical activity of the lithium-rich material is low, a catalyst with a smaller particle size is more useful for the decomposition of the lithium-rich material.
[0012] In one implementation of the present application, the lithium-rich material covers the surface of the catalyst and / or the catalyst is dispersed in the lithium-rich material, thus allowing the catalytic activity of the catalyst to be utilized to a greater extent.
[0013] In one implementation of the present application, the mass ratio of the lithium-rich material to the catalyst is 1:(0.01 to 100). By controlling the mass ratio of the lithium-rich material to the catalyst, the initial delithiation capacity of the positive electrode prelithiation agent can be adjusted.
[0014] In some implementations of the present application, the lithium-rich material forms a lithium-rich material coating layer on the surface of the catalyst having a thickness of 10 nm to 20 μm. When the lithium-rich material covers the catalyst, the catalytic activity of the catalyst can be utilized to a large extent.
[0015] In some implementations of the present application, the cathode prelithiation agent further includes a protective layer wrapped around the catalyst and the lithium-rich material, the protective layer having ion conductivity, and the protective layer can further improve the stability and processing performance of the cathode prelithiation agent, especially when the lithium-rich material is lithium oxide or lithium peroxide.
[0016] In one implementation of the present application, the material of the protective layer includes at least one of lithium fluoride, lithium carbonate, lithium oxalate, lithium acetate, lithium phosphate, inorganic conductive carbon, organic polymer, and passive oxide, which does not increase the risk of gassing by the electrolyte of the battery.
[0017] In one embodiment of the present application, the thickness of the protective layer is in the range of 5 nm to 200 nm. A protective layer of appropriate thickness can ensure high processing performance of the positive electrode prelithiation agent, and can prevent the protective layer from being too thick, affecting the timely release of active lithium, and increasing the battery impedance.
[0018] In one embodiment of the present application, the mass of the protective layer is 0.01% to 10% of the mass of the positive electrode prelithiation agent. Because the mass ratio of the protective layer is low, the positive electrode prelithiation agent can have high processing performance without excessively increasing the mass of the residue remaining after delithiation of the positive electrode prelithiation agent.
[0019] In one implementation of the present application, the particle size of the cathode prelithiation agent ranges from 50 nm to 30 μm.
[0020] A second aspect of the present embodiment further provides a method for preparing a cathode prelithiation agent, the method including: performing lattice reconstruction on an oxide cathode active material to obtain a catalyst, and then performing physical fusion on the catalyst and a lithium-rich material to obtain a cathode prelithiation agent; or mixing an oxide cathode active material and a lithium-rich material, and then performing high-energy ball milling to obtain a cathode prelithiation agent, where the cathode prelithiation agent includes a catalyst and a lithium-rich material, the catalyst is an oxide cathode active material after lattice reconstruction, the intensity ratio of the crystal plane diffraction peak (003) of the catalyst to the crystal plane diffraction peak (104) of the catalyst is less than or equal to 2, the catalyst is configured to catalyze and decompose the lithium-rich material to release active lithium, and the lithium-rich material includes at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate.
[0021] In some implementations of the present application, the lattice reconstruction scheme includes one of the following schemes: (a) subjecting an oxide active cathode material to high energy ball milling; or (b) subjecting an oxide active cathode material and a compound of a Group 3 element and / or a Group 5 element to high energy ball milling, followed by sintering.
[0022] In some implementations of the present application, the rotation speed of the high-energy ball milling is greater than or equal to 350 r / min.
[0023] In some implementations of the present application, the physical fusion is low speed ball milling with a rotation speed less than or equal to 300 r / min.
[0024] In some implementations of the present application, the preparation method further includes forming a protective layer wrapped around the catalyst and the lithium-rich material, particularly when the lithium-rich material includes at least one of lithium oxide and lithium peroxide. In a particular embodiment, the manner of forming the protective layer includes placing the core material obtained by physically fusing the catalyst and the lithium-rich material in a dry air or carbon dioxide atmosphere for heat treatment. In this way, a dense lithium carbonate protective layer can be generated in-situ.
[0025] The method for preparing a cathode prelithiation agent provided in the second aspect of the embodiment of the present application has a simple process, is efficient and environmentally friendly, and can be used for mass production.
[0026] A third aspect of the present embodiment further provides a positive plate for a battery, the positive plate for the battery comprising a current collector and a positive electrode material layer disposed on the current collector, the positive electrode material layer comprising a positive electrode prelithiation agent according to the first aspect of the present embodiment, a positive electrode active material, a binder, and a conductive agent.
[0027] In preparing a positive electrode plate for a battery, the positive electrode slurry used to form the positive electrode material layer has a tunable viscosity and does not undergo gelling, so that it can be easily applied and a highly even film layer is obtained. The electrode plate containing the positive electrode prelithiation agent can be used to provide an electrochemical battery with high energy density and long cycle life.
[0028] A fourth aspect of the present embodiment further provides an electrochemical battery comprising a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode. The positive electrode is a positive plate for the battery according to the third aspect of the present embodiment. The electrochemical battery has a high energy density and a long cycle life.
[0029] A fifth aspect of the present embodiment further provides a terminal. The terminal includes a housing, and a main board and a battery located in the housing. The battery includes an electrochemical battery according to the fourth aspect of the present embodiment, and the electrochemical battery is configured to supply power to the terminal. The terminal may be an electronic product such as a mobile phone, a notebook computer, a tablet computer, a portable device, or an intelligent wearable product. [Brief description of the drawings]
[0030] [Figure 1] FIG. 2 is a schematic diagram of the structure of a positive electrode prelithiation agent according to one implementation of the present application.
[0031] [Figure 2a] FIG. 2 is a schematic diagram of the structure of a positive electrode prelithiation agent according to one implementation of the present application.
[0032] [Figure 2b] FIG. 2 is a schematic diagram of the structure of a positive electrode prelithiation agent according to another implementation of the present application.
[0033] [Figure 2c] FIG. 2 is a schematic diagram of a structure of a positive electrode prelithiation agent according to yet another implementation of the present application.
[0034] [Diagram 3] FIG. 2 is a schematic diagram of a structure of a positive plate for a battery according to an embodiment of the present application.
[0035] [Figure 4] FIG. 2 is a schematic diagram of the structure of a terminal according to an embodiment of the present application;
[0036] [Diagram 5] FIG. 2 is an X-ray diffraction (XRD) diagram of a catalyst contained in a cathode prelithiation agent according to embodiment 1 of the present application.
[0037] [Figure 6] FIG. 2 is an XRD diagram of a cathode prelithiation agent according to embodiment 1 of the present application.
[0038] [Figure 7] 1 shows the charge / discharge characteristics of the positive prelithiation agent (a) and the charge / discharge characteristics of a button cell prepared by mixing the positive prelithiation agent and lithium cobalt oxide (b) according to embodiment 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0039] A lithium-ion battery mainly includes a positive electrode, a negative electrode, an electrolyte, and a separator. All the active lithium in a lithium-ion battery is supplied by the positive electrode material. However, due to the initial Coulombic efficiency of the positive electrode material and the initial Coulombic efficiency of the negative electrode material not matching, and the solid electrolyte interphase film (SEI film) being formed on the surface of the negative electrode during the initial charging of the battery, etc., a part of the active lithium of the positive electrode is consumed in the negative electrode. This leads to the loss of reusable lithium, affects the utilization of the gram capacity of the positive electrode material of the battery, and reduces the battery energy density. In addition, the thickness increase of the SEI due to some irreversible chemical side reactions and the size change of the negative electrode material during the cycling of the battery also causes the consumption of a large amount of active lithium, affecting the service life of the battery. In order to improve the energy density and cycle performance of the lithium-ion battery, etc., the embodiment of the present application provides a positive electrode prelithiation agent with excellent prelithiation effect. Hereinafter, the embodiment of the present application will be described with reference to the accompanying drawings in the embodiment of the present application.
[0040] As shown in FIG. 1, in one embodiment of the present application, a cathode prelithiation agent 100 is provided for a cathode of a battery. The cathode prelithiation agent 100 includes a catalyst 11 and a lithium-rich material 12. The material of the catalyst 11 is an oxide cathode active material. The intensity ratio of the crystal plane diffraction peak (003) of the catalyst 11 to the crystal plane diffraction peak (104) of the catalyst 11 is less than or equal to 2. The catalyst 11 is configured to catalyze and decompose the lithium-rich material 12 to release active lithium. The lithium-rich material 12 includes at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate.
[0041] In one implementation of the present application, the lithium-rich material 12 may cover the surface of the catalyst 11 (as shown in FIG. 1 ) and / or the catalyst 11 may be dispersed (not shown) in the lithium-rich material 12. The catalytic activity of the catalyst 11 may be utilized to a large extent. Furthermore, the lithium-rich material 12 may cover the entire surface of the catalyst 11 (as shown in FIG. 1 ); or may cover only a portion of the surface of the catalyst 11.
[0042] The catalyst 11 in the cathode prelithiation agent is sometimes called "oxide cathode active material after lattice reconstruction." Compared with a general oxide cathode active material, the intensity ratio of the crystal plane diffraction peak (003) of the catalyst 11 obtained by performing lattice reconstruction on the oxide cathode active material to the crystal plane diffraction peak (104) of the catalyst 11 is small, a part of the crystal plane is exposed, the surface is rough, and the catalyst 11 exhibits catalytic activity. Furthermore, the oxide cathode active material after lattice reconstruction has a lower lithiation capacity and a smaller reversible capacity, making it more suitable for prelithiation. In the present application, the catalyst 11 can lower the delithiation potential of the lithium-rich material 12, which originally has a high delithiation potential (in other words, has a low electrochemical activity), so that lithium ions are deintercalated from the lithium-rich material 12 within the operating voltage range of the lithium-ion battery. This achieves the prelithiation effect and expands the selection range of the prelithiation agent. As used herein, the term "delithiation potential" is the minimum voltage at which lithium atoms in a material can be deintercalated into the electrolyte to become active lithium ions.
[0043] Furthermore, the residue remaining on the positive electrode side after the delithiation of the positive electrode prelithiation agent does not increase the risk of gassing by the electrolyte, nor does it increase the impedance of the electrochemical cell. Specifically, after the positive electrode prelithiation agent 100 of the present application is delithiated in the battery formation stage, the catalyst 11 is retained in the positive electrode of the battery. The material of the catalyst 11 is an oxide positive electrode active material, which does not increase the risk of gassing by the electrolyte, does not introduce additional materials into the electrochemical cell, and has a small effect on the impedance of the electrochemical cell. The gaseous delithiation products of some lithium-rich materials (such as lithium oxide, lithium peroxide, lithium carbonate, and lithium oxalate) may be released in the exhaust stage of the battery preparation, which does not occupy the size or mass of the electrochemical cell, and of course does not increase the gassing by the electrolyte. The delithiation products of some other lithium-rich materials (such as lithium fluoride and lithium acetate) also do not increase the risk of gassing by the electrolyte, and can participate in the formation of the negative electrode SEI film of the battery without increasing the impedance of the electrochemical cell. Therefore, the positive electrode prelithiation agent can achieve excellent prelithiation effect, and can sufficiently improve the battery cycle performance and energy density, etc.
[0044] The delithiation potential of the lithium-rich material 12 in this application is usually greater than 4.5 V without a catalyst, which is beyond the standard operating voltage range of a battery, so the lithium-rich material 12 is usually not used for prelithiation. However, under the action of the catalyst 11 in this application, the lithium-rich material 12 can release active lithium at a standard battery operating voltage lower than 4.2 V. Table 1 shows the delithiation potential and theoretical specific capacity of the lithium-rich material 12 without a catalyst. Table 1. Delithiation potentials and theoretical specific capacities of lithium-rich materials without catalyst. [Table 1]
[0045] From Table 1, it can be seen that in the present implementations of the present application, the theoretical specific charge capacity (i.e., delithiation capacity) of the lithium-rich materials 12 is high, exceeding 400 mAh / g, and some are even greater than 1000 mAh / g. In particular, the reversible capacity of these lithium-rich materials 12 is small, and therefore the actual prelithiation capacity is high. The actual prelithiation capacity is the difference between the delithiation capacity and the reversible capacity, and may also be referred to as the "irreversible delithiation capacity." For example, the theoretical delithiation capacity of existing Li2NiO2 is 510 mAh / g, and the measured delithiation capacity at 0.1C is 390 mAh / g. However, the reversible capacity of Li2NiO2 is about 120 mAh / g, and therefore the prelithiation capacity of Li2NiO2 is only 270 mAh / g. However, in this application, the actual prelithiation capacity of the cathode prelithiation agent containing lithium cobalt oxide catalyst and lithium oxalate in a mass ratio of 3:1 can reach 320mAh / g at 0.1C.
[0046] In some implementations of the present application, the lithium-rich material 12 is at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, etc. These lithium-rich materials have high theoretical specific charge capacity, and the positive electrode prelithiation agent including such lithium-rich materials can provide high actual prelithiation capacity, which helps to more desirably improve the battery capacity.
[0047] In one implementation of the present application, the mass ratio of the lithium-rich material 12 to the catalyst 11 may be 1: (0.01-100). In some embodiments, the mass ratio may be 1: (0.1-20). In some other embodiments, the mass ratio may be 1: (0.5-20). In still some other embodiments, the mass ratio of the lithium-rich material 12 to the catalyst 11 may be 1: (2-8). The ratio of the lithium-rich material 12 to the catalyst 11 is controlled to be within a suitable range, so that the initial delithiation capacity and the actual prelithiation capacity of the cathode prelithiation agent 100 can be adjusted. In some implementations of the present application, the initial delithiation capacity of the cathode prelithiation agent may be flexibly selected within a range of 400 mAh / g to 1700 mAh / g. In some embodiments, the initial delithiation capacity of the cathode prelithiation agent may be within a range of 420 mAh / g to 1400 mAh / g. In some other embodiments, this value may be adjusted within a range of 420 mAh / g to 600 mAh / g. For example, when the lithium-rich material is lithium oxide, and the mass ratio of lithium oxide to catalyst is greater than or equal to 1:4, the initial delithiation capacity of the cathode prelithiation agent may be greater than 400 mAh / g.
[0048] In one implementation of the present application, the prelithiation capacity of the positive electrode prelithiation agent 100 is not less than 400mAh / g. The positive electrode prelithiation agent 100 has a high prelithiation capacity, which can fully compensate for the irreversible loss of active lithium in the negative electrode of the battery during preparation and cycling of the battery. This significantly improves the battery energy density and cycle life. In some embodiments, the prelithiation capacity of the positive electrode prelithiation agent 100 may be 400mAh / g to 1300mAh / g. In some other embodiments, the prelithiation capacity of the positive electrode prelithiation agent 100 may be 400mAh / g to 800mAh / g.
[0049] The battery term "battery energy density" refers to the amount of electricity stored in a battery per unit weight or size. Battery energy density can be determined by multiplying the specific capacity of the electrode material by the discharge voltage. This value is essentially equal to the amount of active lithium divided by the total size or mass of the battery. The higher the prelithiation capacity provided by the prelithiation agent, the smaller the residual mass remaining after prelithiation, indicating a larger increase in battery energy density.
[0050] In some implementations of the present application, the lithium-rich material 12 is at least one of lithium oxide, lithium peroxide, lithium carbonate, and lithium oxalate. The delithiation products of these lithium-rich materials are oxygen, nitrogen, or CO2 gas, which may be released during the evacuation stage of battery preparation. In this case, the mass residual degree of the positive prelithiation agent after delithiation (i.e., the ratio of the mass of the residual to the mass of the positive prelithiation agent before delithiation) is low. This causes a very small increase in the size and mass of the battery, which is very helpful in increasing the battery energy density.
[0051] In some implementations of the present application, after the positive electrode prelithiation agent is added, the battery energy density can be increased by 0.5% to 2%, and the cycle life can be increased by 30% to 50%.
[0052] In some implementations of the present application, the intensity ratio of the crystal plane diffraction peak (003) of the catalyst 11 to the crystal plane diffraction peak (104) of the catalyst 11 may be less than or equal to 1.8, for example, in the range of 1.0 to 1.8 or 1.4 to 1.8. The intensity ratio of the crystal plane diffraction peak (003) of the oxide cathode active material without lattice reconstruction to the crystal plane diffraction peak (104) of the oxide cathode active material is usually greater than 2. Compared with the oxide cathode active material, a smaller ratio of the catalyst 11 indicates a higher degree of lattice reconstruction and a higher catalytic activity of the catalyst 11, allowing the lithium-rich material with low electrochemical activity to produce active lithium at a lower delithiation potential.
[0053] In the present application, the oxide cathode active material may be of the undoped type or the doped type. In some implementations of the present application, the oxide cathode active material may include at least one of lithium cobalt oxide, lithium manganate, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganate, lithium nickel cobalt manganate, and lithium nickel cobalt aluminate, etc., but is not limited thereto. Lithium nickel oxide, lithium nickel cobalt manganate, and lithium nickel cobalt aluminate usually have a layered crystal structure, lithium manganate has a spinel structure, and lithium cobalt oxide and lithium nickel manganate may have a layered structure and / or a spinel structure. The general structural formulas of lithium cobalt oxide, lithium manganate, and lithium nickel oxide may be any one of LiMO2, Li2MO2, Li2MO3, Li2MO4, Li3MO4, Li5MO4, and Li6MO4, where M may represent Ni, Co, or Mn.
[0054] In some other implementations of the present application, the oxide positive active material may further include a doping element. In this case, the oxide positive active material belongs to a certain doping type, and the doping element may include at least one of B, P, N, Mg, Al, Ca, Ba, La, Zr, Mo, Nb, Ti, Sn, Sb, Cr, Fe, Cu, and Zn. The lithium nickel cobalt oxide preferably does not include the doping element Al to avoid overlap with the lithium nickel cobalt aluminate ternary material. A suitable doping element may be introduced to achieve at least one of changing the internal electron orbital overlap state or surface properties of the oxide positive active material, improving the structural stability, and the like.
[0055] In some implementations of the present application, the positive electrode prelithiation agent may further include a protective layer 2, and the protective layer 2 is wound around the catalyst 11 and the lithium-rich material 12. When the lithium-rich material 12 is at least one of lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate, these lithium-rich materials have high stability in air, and the protective layer 2 may be provided, or of course the protective layer may not be provided. When the positive electrode prelithiation agent is not provided with the protective layer 2, it is preferable that the lithium-rich material 2 covers the surface of the catalyst 11. In particular, when the lithium-rich material 12 is lithium oxide and / or lithium peroxide, the protective layer 2 may be provided to ensure high processing performance and structural stability of the positive electrode prelithiation agent.
[0056] Specifically, please refer to Figures 2a, 2b, and 2c together. The cathode prelithiation agent 100 has a core housing structure and includes a core 1 and a protective layer 2 wound around the core 1. The core 1 includes a catalyst 11 and a lithium-rich material 12. In the core 1, the lithium-rich material 12 may cover the surface of the catalyst 11 (as shown in Figures 2a and 2c) and / or the catalyst 11 is dispersed in the lithium-rich material 12 (as shown in Figure 2b). That is, the structure of the cathode prelithiation agent 100 may include at least one of the structures shown in Figures 2a to 2c. The lithium-rich material 12 may cover the entire surface of the catalyst 11 (as shown in Figure 2a) or only a portion of the surface of the catalyst 11 (as shown in Figure 2c).
[0057] The protective layer 2 is provided to prevent the catalyst 11 and the lithium-rich material 12 from essentially contacting the air and from absorbing moisture, carbon dioxide, or oxygen in the air, thereby causing a decrease in the prelithiation ability. This further improves the stability of the positive electrode prelithiation agent. Furthermore, compared with lithium-rich materials such as Li2NiO2 and Li6CoO4 in the prior art, the lithium-rich material 12 in the present specification has a low chemical activity and therefore a high structural stability. Furthermore, the protective layer 2 is provided to prevent the lithium-rich material 12 from directly contacting the positive electrode slurry when the alkalinity is high. Therefore, the positive electrode prelithiation agent 100 has high processing performance, is fully compatible with the conventional preparation process for the positive electrode of a lithium-ion battery, and does not reduce the fluidity of the positive electrode slurry or affect the coating effect.
[0058] In one implementation of the present application, the material of the protective layer 2 is a material with ionic conductivity. In this way, it does not affect the subsequent release of active lithium by the lithium-rich material. Optionally, the ionic conductivity of the material constituting the protective layer 2 at room temperature is 10 -8 S cm -1 The material of the protective layer 2 may include at least one of lithium fluoride, lithium carbonate, lithium oxalate, lithium acetate, inorganic conductive carbon, organic polymer, and immobile oxide, etc. Furthermore, in FIG. 2a, FIG. 2b, and FIG. 2c, the material of the protective layer 2 is different from the material of the lithium-rich material 12. The protective layer 2 has high stability in air, is less likely to absorb water, oxygen, etc., and has low alkalinity. The cathode prelithiation agent with the protective layer can have high stability in air and processing performance. Furthermore, after the cathode prelithiation agent is delithiated, the remaining protective layer (except when the protective layer is made of lithium carbonate) does not increase the risk of gas generation by the electrolyte of the battery.
[0059] Specifically, examples of inorganic conductive carbon may be amorphous carbon and graphene; examples of organic polymers may be polyparaxylylene and its derivatives, polyacrylates such as polymethylmethacrylate (PMMA), and polyolefins such as polyethylene (PE) and polystyrene; examples of immobile oxides may be silicon dioxide, oxides of group 1-3 metal elements (such as aluminum oxide, magnesium oxide, and barium oxide), and non-catalytic transition metal oxides (such as titanium dioxide, zinc oxide, zirconia, and tin oxide). When the protective layer 2 is made of inorganic conductive carbon, the conductivity of the positive electrode prelithiation agent can be further improved. When the protective layer 2 is made of lithium carbonate, the positive electrode prelithiation agent decomposes during delithiation to also produce gas, so that a small amount of residue remains after delithiation of the positive electrode prelithiation agent. This further reduces the impact of the positive electrode prelithiation agent on the mass and size of the battery, which helps to improve the battery energy density.
[0060] In one implementation of the present application, the thickness of the protective layer 2 may be within a range of 5 nm to 200 nm. In some implementations of the present application, the thickness of the protective layer 2 may be 10 nm to 100 nm. The thickness of the protective layer 2 may be adjusted based on the size of the core. A protective layer 2 with an appropriate thickness can ensure high processing performance of the positive electrode prelithiation agent 100, and can also prevent the protective layer 2 from being too thick, affecting the timely release of active lithium, increasing the battery impedance, etc.
[0061] In some implementations of the present application, the mass of the protective layer 2 may account for 0.01% to 10% of the mass of the cathode prelithiation agent 100. Due to the low mass percentage, the protective layer can ensure high processing performance of the cathode prelithiation agent. Even if the protective layer 2 is not made of lithium carbonate, the low mass percentage can also ensure that the mass of the residue remaining after delithiation of the cathode prelithiation agent is small.
[0062] In one implementation of the present application, the particle size of the cathode prelithiation agent 100 may be in the range of 50 nm to 30 μm. In some implementations of the present application, the particle size of the cathode prelithiation agent 100 may be in the range of 300 nm to 15 μm.
[0063] In one implementation of the present application, the particle size of the catalyst 11 may be in the range of 10 nm to 25 μm. When the electrochemical activity of the lithium-rich material 12 (e.g., lithium oxide or lithium acetate) is low, the catalyst 11 with a smaller particle size is more useful for the decomposition of the lithium-rich material. In some implementations of the present application, the particle size of the catalyst 11 may be 10 nm to 20 μm, or even 20 nm to 200 nm. For example, in the cathode prelithiation agent shown in FIG. 2a, the particle size of the catalyst 11 may be 100 nm to 1 μm; in the cathode prelithiation agent shown in FIG. 2b, the particle size of the catalyst 11 may be 10 nm to 2 μm, for example, 10 nm to 450 nm. In some other implementations of the present application, as shown in FIG. 2c, the particle size of the catalyst 11 may be 100 nm to 25 μm, for example, 500 nm to 15 μm.
[0064] In some implementations of the present application (as shown in FIG. 1, FIG. 2a, and FIG. 2c), the lithium-rich material 12 covers the surface of the catalyst 11 to form a lithium-rich material coating layer with a certain thickness. When the lithium-rich material 12 covers the catalyst 11, the catalytic activity of the catalyst 11 can be utilized to a large extent. The thickness of the lithium-rich material coating layer can range from 5 nm to 200 nm. Specifically, the thickness can be from 10 nm to 100 nm, or from 20 nm to 90 nm.
[0065] The positive electrode prelithiation agent 100 provided in this embodiment of the present application has high structural stability and high safety performance, and can efficiently release active lithium at the standard operating voltage of the battery (not exceeding 4.2 V), resulting in a high prelithiation capacity. In addition, the residue remaining after delithiation of the positive electrode prelithiation agent 100 does not increase the risk of gas generation by the electrolyte, and does not increase the impedance of the electrochemical cell. This helps to improve the battery cycle performance and energy density.
[0066] Accordingly, one embodiment of the present application further provides a method for preparing a cathode prelithiation agent, the method including the following steps:
[0067] S01: A catalyst is obtained by subjecting an oxide positive electrode active material to lattice reconstruction, in which the intensity ratio of the crystal plane diffraction peak (104) of the catalyst to the crystal plane diffraction peak (003) of the catalyst is less than or equal to 2.
[0068] S02: Physically fusing the catalyst and the lithium-rich material to obtain a cathode prelithiation agent, the catalyst being configured to catalyze and decompose the lithium-rich material to release active lithium, the lithium-rich material including at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate.
[0069] According to this preparation method, a cathode prelithiation material as shown in FIG. 1 may be prepared in which the lithium-rich material covers the catalyst, or a cathode prelithiation material may be prepared in which the catalyst is dispersed in the lithium-rich material.
[0070] In step S01, the lattice reconstruction method includes one of the following methods: (a) subjecting the oxide cathode active material to high energy ball milling; or (b) subjecting the oxide cathode active material and a compound of a group 3 element and / or a group 5 element to high energy ball milling and then sintering. In this application, after subjecting the oxide cathode active material to lattice reconstruction, the surface of the oxide cathode active material becomes rough and the particle distribution changes. Moreover, the oxide cathode active material after lattice reconstruction has a lower lithiation capacity and a lower cycle performance, making it more suitable for pre-lithiation.
[0071] In method a, the oxide cathode active material is subjected to high energy ball milling to damage the original structure of the oxide cathode active material, and the lattice reconstruction of the oxide cathode active material is carried out. In this way, lithium atoms and transition metal atoms are mixed, some of the crystal planes are exposed, and high catalytic activity for catalyzing and decomposing the lithium-rich material is achieved. In method b, the catalyzed lithium-rich material and compounds of group 3 and / or group 5 elements are subjected to high energy ball milling and then sintered. The compounds of group 3 and / or group 5 elements may be used to induce the regeneration of crystals in the catalyzed lithium-rich material, and the preferred crystal orientation is selected for growth and becomes catalytically active. In addition, some of the group 3 and group 5 elements may alternatively be doped into the crystal structure of the oxide cathode active material to function as doping elements. This can improve the structural stability of the obtained catalyst, change the surface properties, etc.
[0072] In one implementation of the present application, the rotation speed of the high-energy ball milling is greater than 350 r / min. In some embodiments, the rotation speed of the high-energy ball milling may be greater than 400 r / min, for example, 400 r / min to 1200 r / min, or 600 r / min to 1000 r / min. In some implementations of the present application, the ball-to-powder ratio during high-energy ball milling may be in the range of (5 to 30):1. The lattice reconstruction can be more desirably performed at a higher ball-to-powder ratio. In some embodiments, the ball-to-powder ratio during high-energy ball milling may be in the range of (10 to 30):1.
[0073] In method b, the group 3 element includes at least one of B, Al, Ga, and In, and the group 5 element includes at least one of N, P, As, Sb, and Bi. The group 3 element and / or the group 5 element may be added in the form of its oxide, nitride, chloride, fluoride, or salt. Specifically, the compound of the group 3 element and / or the group 5 element may be boron oxide, boron fluoride, boron chloride, boric acid, sodium borohydride, aluminum oxide, aluminum hydroxide, aluminum chloride, aluminum carbonate, aluminum fluoride, aluminum sulfide, gallium fluoride, gallium chloride, gallium oxide, magnesium phosphate, aluminum phosphate, iron phosphate, or lithium titanium aluminum phosphate (LATP).
[0074] In some implementations of the present application, in method b, the mass of the compound of group 3 elements and / or group 5 elements may account for 0.05% to 10% of the sum of the mass of the compound and the mass of the oxide positive electrode active material. In some embodiments, the mass ratio is 0.5% to 2%, so that orientation-based regeneration occurs more favorably in the oxide positive electrode active material, and the lattice reconstruction effect can be improved. In method b, sintering may be performed in air, and the sintering temperature may be 500°C to 1000°C, for example, 700°C to 800°C. The sintering time may be 5 hours to 24 hours, for example, 12 hours to 18 hours. The higher the sintering temperature and the longer the sintering time, the more conducive it is to crystal regeneration in the oxide positive electrode active material, and the more crystalline the material is obtained.
[0075] In this embodiment of the present application, in step S02, the manner of physical fusion may be ball milling, sanding, coating, etc. In one implementation of the present application, the manner of physical fusion may be low-speed ball milling, and the rotation speed of the low-speed ball milling is lower than the rotation speed of the high-energy ball milling in step S01. After obtaining the catalyst, the catalyst and the lithium-rich material are subjected to low-speed ball milling to avoid damaging the lattice structure of the formed catalyst. In some implementations of the present application, the rotation speed of the low-speed ball milling is lower than or equal to 300 r / min, for example, 200 r / min to 300 r / min, or 200 r / min to 250 r / min. In some embodiments, the rotation speed of the low-speed ball milling may be lower than 250 r / min. In some implementations of the present application, the low-speed ball milling is performed with a low ball-to-powder ratio. For example, the ball-to-powder ratio during the low-speed ball milling may be in the range of (2 to 10):1. In some implementations of the present application, the diameter of the grinding balls used in the low speed ball milling is less than or equal to 10 mm.
[0076] In another implementation of the present application, the cathode prelithiation agent shown in Figure 1 may alternatively be prepared using a method of mixing an oxide active cathode material and a lithium-rich material followed by high energy ball milling, in which case the lithium-rich material may cover the oxide active cathode material and / or may be dispersed within the lithium-rich material upon lattice reconstruction of the oxide active cathode material.
[0077] In some other implementations of the present application, the preparation method further includes forming a protective layer wrapped around the catalyst and the lithium-rich material, particularly when the lithium-rich material includes at least one of lithium oxide and lithium peroxide.
[0078] Specifically, the method for forming the protective layer may include at least one of physical fusing, physical vapor deposition, chemical vapor deposition, coating, pyrolysis, and in-situ heat treatment. Physical fusing may include ball milling and sanding, etc. Physical vapor deposition may include evaporation deposition and sputtering, etc. The coating method may include one or a combination of dispensing, brushing, spraying, dip coating, blade coating, and spin coating. The coating solution used for coating may be a material directly containing the protective layer; or may be a precursor containing the protective layer material, where the protective layer material may be subsequently obtained by co-precipitation or sol-gel.
[0079] In the present application, the method for forming the protective layer may be selected based on the specific material of the protective layer. The physical fusion and coating methods are suitable for forming protective layers of various materials. The pyrolysis method is particularly suitable for forming a protective layer made of an inorganic conductive carbon material. Specifically, an organic carbon source and a core material (i.e., a catalyst and a lithium-rich material) may be pulverized, and then a high-temperature heat treatment may be performed, so that the organic carbon source undergoes pyrolysis to obtain an inorganic conductive carbon layer. The chemical vapor deposition method is suitable for forming a dense and adhesive protective layer using some organic polymers (e.g., polyparaxylylene and its derivatives, such as paracyclophane).
[0080] In some implementations of the present application, when the lithium-rich material includes at least one of lithium oxide and lithium peroxide, the protective layer may be formed using an in-situ heat treatment method, specifically, by placing the core material in a dry air or carbon dioxide gas stream for in-situ heat treatment. In this way, a dense lithium carbonate protective layer may be generated in-situ after the lithium oxide and / or lithium peroxide undergoes in-situ heat treatment. The in-situ heat treatment method is particularly suitable for preparing the cathode prelithiation agent shown in Figures 2a and 2c. In some embodiments, the temperature of the in-situ heat treatment may be 80°C to 400°C, for example, 100°C, 120°C, 150°C, 180°C, 200°C, 220°C, 250°C, 300°C, 320°C, 350°C, or 400°C. The time of the in-situ heat treatment may be 0.5 hours to 5 hours.
[0081] When the protective layer 2 is provided on the cathode prelithiation agent, and when the lattice reconstruction of the oxide cathode active material is performed by method a, the particle size distribution range of the catalyst is wide, and the particle size ranges from nanometers to micrometers. The particle size of the catalyst prepared by method a is usually in the range of 10 nm to 20 μm. The finally obtained cathode prelithiation agent may have all three structures of FIG. 2a to FIG. 2c. When the particle size of the catalyst is large, the obtained cathode prelithiation agent mainly has the structure shown in FIG. 2c. The particle size of the catalyst obtained by orientation-based growth in method b is small and uniform, and the particle size of the catalyst is usually smaller than 1 μm, for example, in the range of 10 nm to 450 nm. In this case, the cathode prelithiation agent prepared using the catalyst mainly has the structure shown in FIG. 2b, and may also partially have the structure shown in FIG. 2a.
[0082] Of course, if it is necessary to selectively obtain the structures shown in Figures 2a-2c, the particle size concentration of the catalyst may be further controlled before the catalyst obtained in step S01 is mixed with the lithium-rich material. Techniques that can implement particle size concentration include, but are not limited to, cyclosizing, complex frequency sieving, electrostatic grading, and jet grading, etc. In some implementations of the present application, in order to ensure uniform prelithiation ability of different batches of cathode prelithiation agent, the particle size distribution of the catalyst may satisfy the condition of (D90 particle size-D10 particle size) / D50 particle size<1.5.
[0083] The method for preparing the positive electrode prelithiation agent provided in this embodiment of the present application is a simple, efficient and environmentally friendly process, and can be used for mass production.
[0084] As shown in Fig. 3, an embodiment of the present application further provides a positive electrode plate 200 for a battery. The positive electrode plate 200 for a battery includes a current collector 10 and a positive electrode material layer 110 continuously provided on the current collector 10. The positive electrode material layer 110 includes a positive electrode prelithiation agent 100 and a positive electrode active material 101. The positive electrode material layer 110 may further include a binder 102 and a conductive agent 103.
[0085] In one implementation of the present application, the mass of the positive electrode pre-lithiation agent 100 may be 0.1%-40% of the mass of the positive electrode material layer 110. This mass percentage ensures high capacity of the battery prepared using the battery positive electrode plate 200 during initial charge / discharge and multiple non-initial charge / discharge cycles, and the battery has high energy density and long cycle life. In some implementations, the mass percentage is 0.5%-10%.
[0086] In one implementation example of the present application, the cathode material layer 110 may be formed by coating the current collector 10 with a cathode slurry including the cathode prelithiation agent 100, the cathode active material 101, the binder 102, and the conductive agent 103, followed by drying and compression. The cathode prelithiation agent 100 has a protective layer that prevents the catalyst and lithium-rich material in the core material from contacting the binder, etc. In this way, the cathode slurry can be easily applied onto the current collector 10 without causing the gelling phenomenon, and a film layer with high flatness is obtained.
[0087] In one implementation of the present application, the current collector 10 includes, but is not limited to, a metal foil or an alloy foil. The metal foil includes copper foil, titanium foil, aluminum foil, platinum foil, indium foil, ruthenium foil, nickel foil, tungsten foil, tantalum foil, gold foil, or silver foil. The alloy foil includes stainless steel or an alloy including at least one element of copper, titanium, aluminum, platinum, indium, ruthenium, nickel, tungsten, tantalum, gold, and silver. Optionally, the aforementioned elements are the main components of the alloy foil. The metal foil may further include a doping element, including, but not limited to, one or more of platinum, ruthenium, iron, cobalt, gold, copper, zinc, aluminum, magnesium, palladium, rhodium, silver, and tungsten. The current collector 10 may be etched or roughened to form a secondary structure to achieve effective contact with the positive electrode material layer 110.
[0088] In the present application, the positive electrode active material 101 may be at least one of lithium iron phosphate, lithium manganese phosphate, lithium iron manganese phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium cobalt oxide, lithium manganate, lithium nickel manganate, nickel cobalt manganese (NCM), and nickel cobalt aluminum (NCA), and the like.
[0089] In the present application, the binder and conductive agent in the positive electrode material layer 110 are not particularly limited and may be made of existing conventional materials in the art. For example, the binder 102 may be one or more of styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), polypropylene nitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyolefin, carboxymethyl cellulose (CMC), and sodium alginate. For example, the conductive agent 103 may be one or more of conductive carbon black (e.g., acetylene black or ketjen black), furnace black, carbon nanotubes, carbon fibers, and graphene.
[0090] An embodiment of the present application further provides an electrochemical battery including a positive electrode, a negative electrode, a separator, and an electrolyte. The separator and electrolyte are located between the positive electrode and the negative electrode, and the positive electrode is the positive electrode plate 200 for the battery in the above description. The electrochemical battery has a high energy density and a long cycle life.
[0091] The electrochemical battery may be a secondary battery, which has high cycle performance and high safety. In particular, the secondary battery may be a lithium secondary battery.
[0092] As shown in FIG. 4, an embodiment of the present application further provides a terminal 300. The terminal 300 may be a mobile phone, or may be an electronic product such as a tablet computer, a notebook computer, a portable device, or an intelligent wearable product. The terminal 300 includes a housing 301 attached to the outside of the terminal, and a circuit board and a battery (not shown in the figure) located in the housing 301. The battery is the battery provided in the above-mentioned embodiment of the present application. The housing 301 may include a display attached to the front side of the terminal, and a back cover attached to the back side. The battery may be fixed inside the back cover to supply power to the terminal 300.
[0093] The following further describes the embodiments of the present application using several embodiments. [Embodiment 1]
[0094] The preparation of the positive electrode prelithiation agent includes the following:
[0095] To obtain the catalyst, lithium cobalt oxide LiCoO2 is selected as the catalyst precursor and subjected to high-energy ball milling with a ball-to-powder ratio of 20:1 and a rotation speed of 350 r / min for 48 h to carry out lattice reconstruction. Then, the catalyst and lithium-rich material Li2O are mixed in a mass ratio of 4:1 and subjected to general ball milling with a rotation speed of 200 r / min for 6 h. Then, the mixed powder obtained by ball milling is placed in a tube furnace and heated to 400 °C, and dried air is introduced at 60 sccm (60 × 10 -3 slm) for 2 hours. This causes a part of the Li2O to react and form a protective layer of lithium carbonate. The temperature is lowered to room temperature, and then the obtained powder is crushed and sieved to obtain the cathode prelithiation agent.
[0096] Preparing the softback battery includes the following:
[0097] (1) Prepare a positive electrode plate for a battery. Single crystal LiCoO2 with a D50 particle size of 14 μm is used as the positive electrode active material. The positive electrode active material, the positive electrode prelithiation agent, the binder PVDF, and the conductive agent carbon nanotubes (CNTs) are weighed in a mass ratio of 94:2:2:2. First, the PVDF is dissolved in the NMP solvent, and then the CNTs are added and evenly dispersed. Then, the positive electrode active material and the positive electrode prelithiation agent are added simultaneously and evenly dispersed to obtain a positive electrode slurry with a viscosity of 3 Pa·s to 8 Pa·s and a fineness of less than 25 μm. The positive electrode slurry is filtered and then coated on an aluminum foil current collector, and then dried, rolled, and die-cut to obtain a positive electrode plate.
[0098] (2) Prepare the negative plate.
[0099] The negative electrode active material of silica graphite (specific capacity of 500 mAh / g, initial efficiency of 83%), conductive carbon black, styrene butadiene rubber (SBR), and carboxymethyl cellulose (CMC) are dispersed in deionized water in a weight ratio of 96.0:1.0:1.5:1.5 and mixed evenly to obtain the negative electrode slurry. The negative electrode slurry is applied onto a copper foil, dried, compressed, and sliced to obtain the negative electrode plate.
[0100] (3) Assemble the battery. A mixed solution of EC and DEC with 1 mol / L LiPF6 (volume ratio of EC to DEC is 1:1) is used as the electrolyte. A three-layer separator made of PP, PE, and PP is used as the separator. In a glove box, the positive plate, separator, and negative plate are stacked in order and wound into a square unpackaged cell. The unpackaged cell is placed in the battery housing and welded. Then, inject the electrolyte into the battery housing, seal the battery housing, and secure the airbag to obtain a soft-back battery for battery performance testing with a rated capacity of about 2270mAh.
[0101] Before the softback battery is subjected to an electrochemical performance test, the electrochemical cell is subjected to chemical formation to activate the positive and negative active materials in the electrochemical cell, form a stable SEI film on the negative electrode, and improve the self-discharge and charge / discharge performance and storage performance of the battery. In the battery formation stage, gas is generated during the film formation of the electrochemical cell. The positive electrode pre-lithiation agent in embodiment 1 of the present application also generates oxygen gas during delithiation, and the gas enters the airbag. After the chemical formation is completed, the airbag can be cut off, and the cut opening can be closed to obtain the battery to be provided. The specific chemical formation process is as follows: After the temperature is raised to 80°C, the battery is charged at a constant charge / discharge ratio of 0.1C for 12 minutes, then charged at a constant current of 0.5C for 9 minutes, and then charged at 1C for 38 minutes. In the above charging process, the voltage is limited to 4.48V. Then, the battery is discharged at 1.0C for 3 minutes, where the voltage is limited to 3.0V. The temperature is then reduced to 45°C and the battery is charged at a constant current and voltage of 0.2C to 4.48V, where the cut-off voltage is 0.025C. The battery is then discharged at 0.5C for 60 minutes, where the voltage is limited to 3.0V.
[0102] FIG. 5 shows the XRD diagram (b) of the catalyst used in embodiment 1, and the XRD diagram (a) of the catalyst precursor used in embodiment 1. It can be seen from FIG. 5 that the intensity ratio of the crystal plane diffraction peak (003) to the crystal plane diffraction peak (104) in the XRD diagram of LiCoO2 before lattice reconstruction is greater than 2.2; the intensity ratio of the crystal plane diffraction peak (003) to the crystal plane diffraction peak (104) of LiCoO2 after lattice reconstruction (i.e., catalyst) is less than or equal to 2. In FIG. 5(a), this ratio is specifically 1.65. It can be seen that the characteristics of the XRD diagrams of LiCoO2 before lattice reconstruction and LiCoO2 after lattice reconstruction are significantly different, and LiCoO2 after lattice reconstruction has a certain catalytic activity.
[0103] Figure 6 is the XRD diagram of the positive electrode prelithiation agent in embodiment 1. It can be seen from Figure 6 that the characteristic peaks of the catalyst (LiCoO2), the lithium-rich material (Li2O), and the protective layer (lithium carbonate) are shown, which indicates that the composite material including the catalyst, the lithium-rich material, and the protective layer, that is, the positive electrode prelithiation agent, has been successfully prepared.
[0104] In addition, the positive electrode pre-lithiation agent in embodiment 1 is separately assembled into a button-type half cell, and the positive electrode pre-lithiation agent and lithium cobalt oxide are mixed in a ratio of 5%:95% to prepare a button-type half cell, and a charge / discharge test is performed. The results are shown in FIG. 7. FIG. 7 shows the charge / discharge characteristics (a) of the positive electrode pre-lithiation agent in embodiment 1, and the charge / discharge characteristics (b) of a button-type cell prepared by mixing the positive electrode pre-lithiation agent and the positive electrode active material of lithium cobalt oxide in a mass ratio of 5%:95%. The process of separately assembling the positive electrode pre-lithiation agent in embodiment 1 into a button-type half cell is as follows: The positive electrode pre-lithiation agent, acetylene black, and PVDF are weighed in a ratio of 8:1:1, and a solvent is added to prepare a positive electrode slurry. The positive electrode slurry is applied onto an aluminum foil current collector and dried, and then rolled and sliced to obtain a positive electrode plate. A half cell is prepared by using the positive plate together with a lithium metal sheet, a mixed solution of EC and DEC with 1 mol / L LiPF6 (volume ratio of EC to DEC is 1:1) as the electrolyte, and a three-layer separator made of PP, PE, and PP as the separator. A charge / discharge test is performed on the half cell with a charge / discharge ratio of 0.05C, and the test voltage range of the positive plate is 3V-4.5V.
[0105] It can be seen from FIG. 7(a) that the positive prelithiation agent can contribute a delithiation capacity of about 500 mAh / g in the initial delithiation, and the reversible capacity (i.e., discharge capacity) is less than 50 mAh / g. Therefore, it can be determined by calculation that the prelithiation capacity of the positive prelithiation agent is greater than 450 mAh / g. It can be seen from FIG. 7(b) that the initial charge capacity of the button cell obtained by mixing the positive prelithiation agent and lithium cobalt oxide can reach 210 mAh / g, and the charge capacity of the button cell made only of lithium cobalt oxide is 180 mAh / g. It can be seen that a positive prelithiation agent with a proportion of 5% provides an additional capacity of about 30 mAh / g to the positive electrode during the initial charge of the cell.
[0106] The residue remaining after delithiation of the cathode prelithiation agent in embodiment 1 of the present application is a trace amount of LiCoO2 particles, and the particle size of the LiCoO2 particles is distributed between 50 nm and 20 μm. [Embodiment 2]
[0107] The preparation of the positive electrode prelithiation agent includes the following:
[0108] Commercially available lithium cobalt oxide powder with particle size in the range of 2μm-50μm is selected as the catalyst precursor, and boron oxide powder and lithium aluminum titanium phosphate (LATP) powder are added to the lithium cobalt oxide powder to obtain a mixed powder. Here, the mass of boron oxide powder and the mass of LATP powder each account for 1% of the mass of the mixed powder. The mixed powder is placed in a ball mill and subjected to high-energy ball milling with a ball-to-powder ratio of 15:1 and a rotation speed of 380r / min for 12 hours. Then, the mixed powder is transferred to a tube furnace and sintered at 700℃ in an air atmosphere for 8 hours, crushed and sieved to obtain the lithium cobalt oxide after lattice reconstruction, i.e., the catalyst. The particle size of the catalyst is 10nm-2μm, and the intensity ratio of the crystal plane diffraction peak (003) of the catalyst to the crystal plane diffraction peak (104) of the catalyst is 1.55.
[0109] The catalyst and lithium-rich material Li2O are mixed in a mass ratio of 3:1, and then subjected to general ball milling at a rotation speed of 250r / min for 3 hours. The mixed powder obtained by ball milling is then taken out, crushed and sieved to obtain the core material. γAl2O3 nanopowder (mass proportion of 0.2%) with a D50 particle size of 30nm is added to the core material, and then subjected to ball milling at a ball-to-powder ratio of 2:1 and a rotation speed of 150r / min for 2 hours, and then crushed and sieved to obtain the positive electrode prelithiation agent.
[0110] The cathode prelithiation agent in embodiment 2 includes the structure shown in FIG. 2b, in which the thickness of the protective layer is 20 nm, the core includes lithium oxide dispersed in the lithium oxide and a catalyst, and the catalyst has a flat shape and a D50 particle size of about 200 nm.
[0111] According to the method described in embodiment 1, the positive pre-lithiation agent in embodiment 2 is used to prepare a softback battery with a rated capacity of about 2270 mAh. [Embodiment 3]
[0112] The preparation of the positive electrode prelithiation agent includes the following: To obtain the catalyst, lithium cobalt oxide LiCoO2 material with particle size in the range of 5μm-20μm (D50 particle size of 14μm) is selected as the catalyst precursor, and lattice reconstruction is carried out by high-energy ball milling with a ball-to-powder ratio of 10:1 and a rotation speed of 400r / min for 14 hours; the catalyst and lithium oxalate Li2C2O4 are mixed in a mass ratio of 3:1, and low-speed ball milling with a ball-to-powder ratio of 8:1 and a rotation speed of 200r / min for 8 hours; the obtained powder is crushed and sieved to obtain the positive electrode prelithiation agent.
[0113] The structure of the positive electrode prelithiation agent in embodiment 3 may be shown in FIG. 1, where the positive electrode prelithiation agent includes a catalyst (lithium cobalt oxide after lattice reconstruction) and a lithium-rich coating layer Li2C2O4 wrapped around the catalyst. The intensity ratio of the crystal plane diffraction peak (003) of the catalyst to the crystal plane diffraction peak (104) of the catalyst is 1.7. The thickness of the Li2C2O4 layer is about 0.5 μm. The particle size of the prelithiation agent is 5.5 μm to 25 μm, and the D50 particle size of the prelithiation agent is about 15 μm.
[0114] According to the method described in embodiment 1, the positive pre-lithiation agent in embodiment 3 is used to prepare a softback battery with a rated capacity of about 2270 mAh. [Embodiment 4]
[0115] The preparation of the positive electrode prelithiation agent includes the following: Selecting lithium cobalt oxide LiCoO2 material with particle size in the range of 5 μm to 20 μm (D50 particle size is 14 μm) as the catalyst precursor; Mixing the catalyst precursor and lithium-rich material LiF in a mass ratio of 1:1, and performing high-energy ball milling with a ball-to-powder ratio of 20:1 and a rotation speed of 350 r / min for 48 hours; Then grinding and sieving the obtained powder to obtain the positive electrode prelithiation agent. The positive electrode prelithiation agent includes a catalyst (lithium cobalt oxide after lattice reconstruction) and a lithium-rich coating layer LiF wrapped around the catalyst. The intensity ratio of the crystal plane diffraction peak (003) of the catalyst to the crystal plane diffraction peak (104) of the catalyst is 1.45. The thickness of the LiF layer is about 2 μm. The D50 particle size of the prelithiation agent is about 18 μm.
[0116] According to the method described in embodiment 1, the positive prelithiation agent in embodiment 4 is used to prepare a softback battery with a rated capacity of about 2270 mAh. [Embodiment 5]
[0117] The preparation of the positive electrode prelithiation agent includes the following: Select NCM811 single crystal material with particle size in the range of 5μm-30μm (D50 particle size is 14μm) as the catalyst precursor. To obtain the catalyst, the catalyst precursor is subjected to high-energy ball milling with a ball-to-powder ratio of 30:1 and a rotation speed of 400r / min for 48 hours to carry out lattice reconstruction. Then, the catalyst and lithium-rich material Li2O are mixed in a mass ratio of 4:1 and subjected to general ball milling with a rotation speed of 250r / min for 3 hours. Then, the mixed powder obtained by ball milling is placed in a tubular furnace. Dry CH4 gas is continuously injected, and then a vacuum degassing process is carried out. The aforementioned process is repeated three times to remove the air in the tubular furnace. Then, the flow rate of CH4 gas is controlled at 10mL / min, and the furnace temperature is increased to 900℃ and held for 4 hours to complete the coating of graphitized carbon. After the furnace temperature is lowered to room temperature, the powder is taken out, and the obtained powder is crushed and sieved to obtain the positive electrode prelithiation agent.
[0118] The positive electrode prelithiation agent in embodiment 5 includes the structure shown in Figure 2a and Figure 2c, where the D50 particle size of the core NCM811 is 14 μm, the thickness of the coating layer formed by coating the surface of NCM811 with lithium oxide is 1.5 μm, and the thickness of the graphitized carbon protective layer is 20 nm. The residue remaining after delithiation of the positive electrode prelithiation agent in embodiment 5 is NCM811 particles and carbon graphitized carbon.
[0119] With reference to the methods in embodiments 1 to 5, a cathode prelithiation agent material in another embodiment is prepared based on the parameters listed in Table 2, providing a material in which the catalyst does not cause lattice reconstruction under the same conditions as the comparative example. According to the preparation method of the button half cell in embodiment 1, a button cell is prepared using the prelithiation agent in each embodiment and the corresponding prelithiation agent in the comparative example. A charge / discharge test is performed on the button cell at a rate of 0.05C within a voltage range of 3V to 4.5V, and the charge / discharge characteristics of each button cell are tested to calculate the charge gram capacity (i.e., the specific delithiation capacity) of each prelithiation agent. The results are shown in Table 2. [Table 2, Structural parameters and charge gram capacity of prelithiation agent] [Table 2]
[0120] The test results in Table 2 show that if the catalyst does not undergo lattice reconstruction, it essentially has no ability to catalyze lithium-rich materials. As a result, the obtained composite material has a very low charge gram capacity and essentially no prelithiation ability.
[0121] In order to further highlight the beneficial effects of the embodiment of the present application, according to the preparation method of the soft-pack full cell in embodiment 1, the positive electrode pre-lithiation agent in the above-mentioned embodiment and the positive electrode active material lithium cobalt oxide are mixed in a mass ratio of 2%:98% to prepare a soft-pack battery. At a constant temperature of 25°C and a charge / discharge ratio of 0.7C, the battery is subjected to the electrochemical performance test in Table 3. Here, the test voltage range is 3V~4.48V (vs.Li / Li+). In addition, the present application further provides the performance test results of a lithium cobalt oxide battery (Comparative Example 1) with the addition of a conventional positive electrode pre-lithiation agent Li2NiO2 and a lithium cobalt oxide full cell (Comparative Example 2) without the addition of the positive electrode pre-lithiation agent in the embodiment of the present application under the same conditions. [Table 3, Battery performance test results] [Table 3]
[0122] It can be seen from Table 3 that the introduction of the positive electrode prelithiation agent in the embodiment of the present application significantly improves the battery cycle performance, and also improves the battery energy density and initial coulombic efficiency to a certain extent. Furthermore, when the mass ratio of the positive electrode prelithiation agent in the embodiment of the present application to the positive electrode active material is the same as the mass ratio of the conventional prelithiation agent Li2NiO2 to the positive electrode active material, the positive electrode prelithiation agent in the embodiment of the present application can more favorably improve the battery energy density, initial coulombic efficiency, and cycle life compared with the conventional prelithiation agent Li2NiO2. [Item 1] 1. A cathode prelithiation agent, comprising: a catalyst and a lithium-rich material, wherein the catalyst is an oxide cathode active material, an intensity ratio of a crystal plane diffraction peak (003) of the catalyst to a crystal plane diffraction peak (104) of the catalyst is less than or equal to 2, and the catalyst is configured to catalyze and decompose the lithium-rich material to release active lithium, and the lithium-rich material comprises at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate. [Item 2] 2. The cathode prelithiation agent according to item 1, wherein the intensity ratio of the crystal plane diffraction peak (003) of the catalyst to the crystal plane diffraction peak (104) of the catalyst ranges from 1.0 to 1.8. [Item 3] Item 2. The cathode prelithiation agent according to item 1, wherein the oxide cathode active material comprises at least one of lithium cobalt oxide, lithium manganate, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganate, lithium nickel cobalt manganate, and lithium nickel cobalt aluminate. [Item 4] Item 4. The cathode prelithiation agent according to item 3, wherein the oxide cathode active material further comprises a doping element, the doping element comprising at least one of B, P, N, Mg, Al, Ca, Ba, La, Zr, Mo, Nb, Ti, V, Sn, Sb, Cr, Fe, Cu, and Zn. [Item 5] 2. The cathode prelithiation agent according to item 1, wherein the particle size of the catalyst ranges from 10 nm to 25 μm. [Item 6] 6. The cathode prelithiation agent according to any one of the preceding claims, wherein the lithium-rich material covers a surface of the catalyst and / or the catalyst is dispersed within the lithium-rich material. [Item 7] 7. The positive electrode prelithiation agent according to item 6, wherein the mass ratio of the lithium-rich material to the catalyst is 1:(0.01-100). [Item 8] 7. The positive electrode prelithiation agent according to item 6, wherein the lithium-rich material forms a lithium-rich material coating layer having a thickness of 10 nm to 20 μm on the surface of the catalyst. [Item 9] Item 9. The cathode prelithiation agent according to any one of items 1 to 8, wherein the cathode prelithiation agent further comprises a protective layer wrapped around the catalyst and the lithium-rich material, the protective layer having ionic conductivity. [Item 10] 10. The positive electrode prelithiation agent according to item 9, wherein the material of the protective layer comprises at least one of lithium fluoride, lithium carbonate, lithium oxalate, lithium acetate, lithium phosphate, inorganic conductive carbon, organic polymer, and passive oxide. [Item 11] 11. The cathode prelithiation agent according to item 9 or 10, wherein the thickness of the protective layer ranges from 5 nm to 200 nm. [Item 12] 12. The positive electrode prelithiation agent according to any one of items 9 to 11, wherein a mass of the protective layer is 0.01% to 10% of a mass of the positive electrode prelithiation agent. [Item 13] Item 13. The cathode prelithiation agent according to any one of items 1 to 12, wherein the particle size of the cathode prelithiation agent ranges from 50 nm to 30 μm. [Item 14] 1. A method for preparing a cathode prelithiation agent, the method comprising: performing lattice reconstruction on the oxide cathode active material to obtain a catalyst, and physically fusing the catalyst and the lithium-rich material to obtain a cathode prelithiation agent; or Mixing the oxide cathode active material and the lithium-rich material, and then performing high-energy ball milling to obtain a cathode prelithiation agent, wherein the cathode prelithiation agent comprises a catalyst and the lithium-rich material, and the catalyst is the oxide cathode active material after lattice reconstruction. Equipped with a ratio of an intensity of a crystal plane diffraction peak (003) of the catalyst to a crystal plane diffraction peak (104) of the catalyst is less than or equal to 2, the catalyst is configured to catalyze decomposition of the lithium-rich material to release active lithium, the lithium-rich material comprising at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate. [Item 15] Item 15. The method of preparing according to item 14, wherein the lattice reconstruction is performed by one of the following methods: (a) subjecting the oxide cathode active material to high energy ball milling; or (b) subjecting the oxide cathode active material and a compound of a group 3 element and / or a group 5 element to high energy ball milling, followed by sintering. [Item 16] 16. A positive electrode plate for a battery, the positive electrode plate for the battery comprising a current collector and a positive electrode material layer provided on the current collector, the positive electrode material layer comprising the positive electrode prelithiation agent according to any one of items 1 to 15, a positive electrode active material, a binder, and a conductive agent. [Item 17] Item 17. The battery positive plate according to item 16, wherein the mass of the positive electrode prelithiation agent is 0.1% to 40% of the mass of the positive electrode material layer. [Item 18] 18. An electrochemical battery comprising a positive electrode, a negative electrode, and a separator and an electrolyte located between the positive electrode and the negative electrode, the positive electrode being the positive plate for a battery according to item 16 or 17. [Item 19] 20. A terminal comprising a housing, and a main board and a battery located within the housing, the battery including the electrochemical battery of item 18, the electrochemical battery configured to supply power to the terminal.
Claims
1. A cathode prelithiation agent, the cathode prelithiation agent comprising a catalyst and a lithium-rich material, the catalyst being an oxide cathode active material, the catalyst having an intensity ratio of a crystal plane diffraction peak (003) of the catalyst to a crystal plane diffraction peak (104) of the catalyst being less than or equal to 2, the catalyst being configured to catalyze and decompose the lithium-rich material to release active lithium, the lithium-rich material comprising at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate; The cathode prelithiation agent further comprises a protective layer wrapped around the catalyst and the lithium-rich material, the protective layer having ion conductivity.
2. The positive electrode prelithiation agent described in claim 1, wherein the material of the protective layer includes at least one of lithium fluoride, lithium carbonate, lithium oxalate, lithium acetate, lithium phosphate, inorganic conductive carbon, organic polymer, and immobile oxide.
3. The cathode prelithiation agent of claim 1, wherein the protective layer has a thickness ranging from 5 nm to 200 nm.
4. A positive electrode prelithiation agent described in any one of claims 1 to 3, wherein the mass of the protective layer is 0.01% to 10% of the mass of the positive electrode prelithiation agent.
5. A cathode prelithiation agent, comprising a catalyst and a lithium-rich material, the catalyst being an oxide cathode active material, an intensity ratio of a crystal plane diffraction peak (003) of the catalyst to a crystal plane diffraction peak (104) of the catalyst being less than or equal to 2, the catalyst being configured to catalyze and decompose the lithium-rich material to release active lithium, the lithium-rich material comprising at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate, the lithium-rich material covers the surface of the catalyst and / or the catalyst is dispersed within the lithium-rich material; a mass ratio of said lithium-rich material to said catalyst of 1:(0.01-100);
6. A cathode prelithiation agent, comprising a catalyst and a lithium-rich material, the catalyst being an oxide cathode active material, an intensity ratio of a crystal plane diffraction peak (003) of the catalyst to a crystal plane diffraction peak (104) of the catalyst being less than or equal to 2, the catalyst being configured to catalyze and decompose the lithium-rich material to release active lithium, the lithium-rich material comprising at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate, the lithium-rich material covers the surface of the catalyst and / or the catalyst is dispersed within the lithium-rich material; a positive electrode prelithiation agent, wherein the lithium-rich material forms a lithium-rich material coating layer having a thickness of 10 nm to 20 μm on the surface of the catalyst;
7. 7. The cathode prelithiation agent according to any one of claims 1 to 6, wherein the intensity ratio of the crystal plane diffraction peak (003) of the catalyst to the crystal plane diffraction peak (104) of the catalyst ranges from 1.0 to 1.
8.
8. 8. The cathode prelithiation agent of claim 1, wherein the oxide cathode active material comprises at least one of lithium cobalt oxide, lithium manganate, lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel manganate, lithium nickel cobalt manganate, and lithium nickel cobalt aluminate.
9. 9. The cathode prelithiation agent of claim 8, wherein the oxide cathode active material further comprises a doping element, the doping element comprising at least one of B, P, N, Mg, Al, Ca, Ba, La, Zr, Mo, Nb, Ti, V, Sn, Sb, Cr, Fe, Cu, and Zn.
10. The cathode prelithiation agent according to any one of claims 1 to 9, wherein the particle size of the catalyst ranges from 10 nm to 25 μm.
11. The cathode prelithiation agent according to any one of claims 1 to 10, wherein the particle size of the cathode prelithiation agent ranges from 50 nm to 30 μm.
12. 1. A method for preparing a cathode prelithiation agent, the method comprising: performing lattice reconstruction on the oxide cathode active material to obtain a catalyst, and physically fusing the catalyst and the lithium-rich material to obtain a cathode prelithiation agent; or Mixing the oxide cathode active material and the lithium-rich material, and then performing high-energy ball milling to obtain a cathode prelithiation agent, wherein the cathode prelithiation agent comprises a catalyst and the lithium-rich material, and the catalyst is the oxide cathode active material after lattice reconstruction. Equipped with a ratio of an intensity of a crystal plane diffraction peak (003) of the catalyst to a crystal plane diffraction peak (104) of the catalyst is less than or equal to 2, the catalyst is configured to catalyze decomposition of the lithium-rich material to release active lithium, the lithium-rich material comprising at least one of lithium oxide, lithium peroxide, lithium fluoride, lithium carbonate, lithium oxalate, and lithium acetate.
13. 13. The method of claim 12, wherein the lattice reconstruction comprises one of: (a) subjecting the oxide active cathode material to high energy ball milling; or (b) subjecting the oxide active cathode material and a compound of a Group 3 element and / or a Group 5 element to high energy ball milling followed by sintering.
Citation Information
Patent Citations
Positive-electrode active material for lithium secondary cell
WO2016035853A1
Li-ni composite oxide particle powder and nonaqueous electrolyte secondary battery
WO2019168160A1